Climate change adaptation strategies adopted by pastoralists in rangelands in Golestan province, Iran - Bahareh Behmanesh; Mohsen Sharaftmandrad; Mohammadreza Shahraki; Hossein Badripour (Scientific Reports, 2025)
Abstract Climate change is a serious challenge to pastoralism in rangelands. Adaptation strategies adopted by pastoralists can reduce their livelihood vulnerability to cope with adverse effects of climate change. This study was done to investigate the adaptation strategies of pastoralists in the north of Golestan province, Iran. Data were collected using a researcher-made questionnaire. The statistical population consisted of 200 pastoralists from 3 pastoral units, of which 127 individuals were sampled using stratified random method. The results showed that 33.1% of the pastoralists had moderate adaptability to climate change. They had more adaptive capacity in cost saving and improving savings, health and veterinary services, and use of technology. The pastoralists’ adaptability to climate change was enhanced with increasing age. Large and less-educated pastoralists had more adaptability compared to small and well-educated ones. Pastoralists who had jobs other than animal-husbandry and who participated in educational and extension courses on climate change had more adaptability to climate change. Pastoralists owning agricultural lands and local knowledge in dealing with climate change were also more adaptable to climate change. The results of the study can be used to strengthen pastoralists’ adaptability to climate change to reduce their livelihood vulnerability.